Strategi Pengembangan Ekowisata Berkelanjutan terhadap Kesejahteraan Masyarakat Lokal di Taman Nasional Sebangau Kota Palangka Raya - Meisa Putri; Icha Ayudiany; Neysya Rosyana; Fitriana Selvia; Marvy Ferdian Agusta Sahay; Imanuel Jaya (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of sustainable tourism and ecotourism plays a crucial role in maintaining a balance between economic growth and environmental conservation through collaboration with local communities. This study aims to analyze ecotourism development in Sebangau National Park and the forms of cooperation that have been established with local communities. The results indicate that development is being carried out gradually through a zoning system that positions communities as key stakeholders in tourism. Although these activities have proven to provide economic benefits to the community, ecotourism development in this region still faces significant challenges related to promotion and accessibility.